Investigation of the Gas Sensing Potential of Electrospun Expanded Polystyrene/ Reduced Graphene Oxide Nanofiber Composites - Okparaocha Funmilayo Joke; Ipeaiyeda Ayodele Rotimi; Mamookho Elizabeth Makhatha; Oyeleke Peter Olaoye; Shorinmade Adijat Yetunde; Obero Ofunami Joy; Oluwasusi Taye Victoria; Abejide Tolulope Bayode; Abdulrahman Abdulsemiu Ayantunde (Chemical and Materials Sciences - Developments and Innovations Vol. 2, 2024)
The gas sensing potential of electrospun nanofiber composites consisting of expanded polystyrene (EPS) and carbon-based nanofillers was investigated in this study. The nanofiber composites of expanded polystyrene (EPS) and reduced graphene oxide (RGO), EPS and carbon black (CB), and hybrid EPS/CB/RGO were produced by solution mixing followed by electrospinning. The surface morphologies of the developed nanofibers were studied with SEM, and the percolation threshold was determined with Keithely 2000 multimeter with four-point probes. The gas-sensing behavior was investigated in a gas-sensing unit. The SEM micrographs revealed long, uniform, and continuous nanofibers without beads or spindles. Homogenous dispersion of the nanofillers in the polymer matrix was also observed. Low percolation thresholds of between 0.07 and 0.2 wt.% were observed for the EPS/RGO composite and 2.0 wt.% for the EPS/CB composite. EPS/RGO sensor exhibited good stability but moderate sensitivity on exposure to the analyte gases. The hybrid composite; EPS/CB/RGO showed improved sensitivity than the others and comparable stability to EPS/RGO. The EPS/CB suffered from instability in response as a result of variations in baseline resistance. A rapid response time of 19s and a short recovery time of 20s were recorded with EPS/CB/RGO exposure to ethanol. The EPS/RGO sensor shows good linearity and reproducibility with a regression coefficient of 0.8975 with ethanol and 0.961 with toluene.